Dilute Solution Viscometry Studies on a Therapeutic Mixture of Non-digestible Carbohydrates - Harding, Stephen; Almutairi, Fahad; Adams, Gary G.; Morris, Gordon; Lawson, Christopher J.; Gahler, Roland J.; Wood, Simon (International Journal of Biotechnology for Wellness Industries, 2012)
Recent work has shown the beneficial effects of a proprietary mixture of three non-digestible carbohydrates: konjac glucomannan, xanthan and alginate and these effects have been linked with a synergistic interaction observable with analytical ultracentrifugation, rheological and NMR measurements. These observations have been supported by fundamental dilute solution viscosity studies. Preparations of konjac glucomannan, xanthan and alginate have been checked with regards their molecular integrity (molar mass distribution) using a newly established method based on the analytical ultracentrifuge. The intrinsic viscosity behaviour for each of the individual polysaccharides were estimated at low ionic strength I (10-3M) and found to be (2090±120) ml/g, (4430±340) ml/g and (3460±330) ml/g for konjac glucomannan, xanthan and alginate respectively and at (10-1M) (2350±200) ml/g, (3370±310) ml/g and (1210±50) ml/g respectively. The intrinsic viscosity [h] was then determined for a proprietary mixture of the three (known as “PGX®”) at both ionic strengths and compared with the predicted values for a non-interacting mixture. In I=10-3 M solvent a significant difference was observed (3090+250) ml/g compared with the predicted value (2350+300) ml/g, although at higher ionic strength the interaction appears to have gone: [h] = (1990+250) ml/g compared with the predicted value of (2180+300) ml/g. This appears to reinforce the earlier observations that in PGX® there is a synergistic interaction which is ionic strength sensitive.